Cold War Era Coup D’etats and the USA: The Cases of Turkey and Greece - Çolakoğlu, Emre Feyzi (Ankara Yıldırım Beyazıt Üniversitesi, 2018)
Turkey and Greece, despite taking part in the democratic Western block, have beensubjected to anti-democratic governments for a period of time after the coup d’étatsthat had taken place on May 27, 1960 in Turkey and April 21, 1967 in Greece. Thecoup d’états in two the NATO countries that had advanced alliance relationship withthe block leader US in this period came naturally attracting to many researchers. Inthis sense, there are various research questions that push researchers to work on thissubject. “Whether the US governments were aware of the coming coup d’états inTurkey and Greece in advance” and “what are the factors that determine therelationships US administrations established with the military rules after the coupd’états had carried out” are at the beginning of these questions. This study seeks toprovide a more multidimensional explanation for the subject research questionsusually discussed from a single perspective in the literature comparatively.

Türkiye ve Yunanistan Soğuk Savaş döneminde ABD’nin başını çektiği demokratikBatı bloğu içerisinde yer almalarına rağmen sırasıyla 27 Mayıs 1960 ve 21 Nisan 1967tarihlerinde gerçekleşen darbelerin ardından bir süre anti-demokratik yöntemlerleyönetilmişlerdir. Bu dönemde blok lideri ABD ile ileri düzeyde müttefiklik ilişkisibulunan iki NATO ülkesinde meydana gelen darbeler doğal olarak pek çokaraştırmacının da ilgisini çekmiştir. Bu anlamda, araştırmacıları bu konu üzerindeçalışmaya iten çeşitli araştırma soruları bulunmaktadır. Bu soruların başında ise ABDyönetimlerinin Türkiye ve Yunanistan’da meydana gelen darbelerden daha öncedenhaberdar olup olmadıkları ile ABD hükümetlerinin darbe sonrasında askeriyönetimlerle kurdukları ilişkileri belirleyen faktörlerin neler olduğu gelmektedir. Buçalışma, söz konusu araştırma sorularına karşılaştırmalı olarak yanıt aramayaçalışarak, literatürde genellikle tek pencereden ele alınan olaylara çok yönlüaçıklamalar getirmeyi amaçlamaktadır.
Soğuk Savaş Dönemi Askeri Darbeleri ve ABD: Türkiye ve Yunanistan Örnekleri
Keywords: Political Science; Siyaset Bilimi